2022
DOI: 10.3390/antiox11091827
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Potential of the Sweet Whey-Based Beverage Colada after the Digestive Process and Relationships with the Lipid and Protein Fractions

Abstract: Whey-based beverages could be an effective way of reusing a by-product of th cheese industry, mitigating environmental hazards and, at the same time, profiting a useful food with high nutritional and antioxidant properties. In this study, a traditional Ecuadorian beverage (Colada) was prepared combining sweet whey, Maracuyá and barley. Antioxidant properties before and after an in vitro digestion using the INFOGEST method were determined, and relationships with intestinal transformations of the lipid and prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 76 publications
1
2
0
Order By: Relevance
“…In line with our results, there are other studies that report a significantly increased antioxidant activity of WPI after digestion, regardless of the assay used [37,54]. In addition, Garcia-Casas et al [55] demonstrated that the bioaccessible fraction (corresponding to the SW-D samples of our study) of a SW-based beverage digestate exhibited an augmented antioxidant activity based on ABTS and FRAP. Since antioxidant compounds can use different mechanisms of action and each of the methods used evaluates their effect in a unique way, their evaluation of said compounds is complementary to each other.…”
Section: Assessment Of Antioxidant Activity Of Sw Before and After In...supporting
confidence: 92%
“…In line with our results, there are other studies that report a significantly increased antioxidant activity of WPI after digestion, regardless of the assay used [37,54]. In addition, Garcia-Casas et al [55] demonstrated that the bioaccessible fraction (corresponding to the SW-D samples of our study) of a SW-based beverage digestate exhibited an augmented antioxidant activity based on ABTS and FRAP. Since antioxidant compounds can use different mechanisms of action and each of the methods used evaluates their effect in a unique way, their evaluation of said compounds is complementary to each other.…”
Section: Assessment Of Antioxidant Activity Of Sw Before and After In...supporting
confidence: 92%
“…Folin-Ciocâlteu methods are commonly used for the quantitation of total polyphenol content, and previous optimization studies had higher confidence in this technique [16,17]. Polar components extracted in alcohol solvents amino acid content in whey-based polyphenol extracts showed no interference with total polyphenol values tested by the Folin-Ciocâlteu method [18]. Previous UHPLC-MS studies done by this research team using in vitro and in vivo assays reported that the most abundant polyphenol compounds, of a total of 16 chromatographically identified compounds in passion fruit, were phenolic acids, xanthines, catechins, anthocyanins, (+)-catechin, (−)epicatechin, ferulic acid, cyanidin 3-rutinoside, and quercetin 3-glucoside.…”
Section: Discussionmentioning
confidence: 99%
“…Mann et al revealed that flavoured milk drinks fortified with 1% or 2% whey protein hydrolysate showed antioxidant activity (13). Contrary to this Garcia-Casas et al reported that adding whey protein to a beverage rich in polyphenols with antioxidant properties does not create additional antioxidant activity (14). The optimal dosage of whey proteins that should be taken depends on the objectives of individuals, the amount of physical activity, and the composition of the body.…”
Section: Discussionmentioning
confidence: 99%